Stem cell‐directed therapies for osteoarthritis: The promise and the practice. (7th February 2020) - Ng, Jia; Little, Christopher B.; Woods, Susan; Whittle, Samuel; Lee, Francis Y.; Gronthos, Stan; Mukherjee, Siddhartha; Hunter, David J.; Worthley, Daniel L.
Abstract: Osteoarthritis (OA) is a disease of an entire synovial joint characterized by clinical symptoms and distortion of joint tissues, including cartilage, muscles, ligaments, and bone. Although OA is a disease of all joint tissues, it is a defined accessible compartment and is thus amenable to topical surgical and regenerative therapies, including stem cells. All tissues arise from stem progenitor cells, and the relative capacity of different cellular compartments, and different individuals, to renew tissues into adulthood may be important in the onset of many different degenerative diseases. OA is driven by both mechanical and inflammatory factors, but how these factors affect the proliferation and differentiation of cells into cartilage in vivo is largely unknown. Indeed, our very basic understanding of the physiological cellular kinetics and biology of the stem‐progenitor cell unit of the articular cartilage, and how this is influenced by mechano‐inflammatory injury, is largely unknown. OA seems, rather deceptively, to be the low‐hanging fruit for stem cell therapy. Without the basic understanding of the stem cell and progenitor unit that generate and maintain articular cartilage in vivo, we will continue to waste opportunities to both prevent and manage this disease . In this review, we discuss the biology of chondrogenesis, the stem cell populations that support articular cartilage in health and disease, and future opportunities afforded through the translation of basic articular chondrocyte stem cell biology into new clinical therapies.